JENIS-JENIS JAMUR MAKRO YANG TERDAPAT DI PERKEBUNAN SAWIT KENAGARIAN DAMAR RUMPUT KECAMATAN AIRPURA KABUPATEN PESISIR SELATAN - Yunita, Ice Putri (STKIP PGRI Sumbar, 2014)
Fungi is eukaryotic organism (has sterling nucleus), has not chlorophyll, has spore of somatic structure or talus that is unicellular and exactly form filament or branch thread (multicelluler), life with asexual and sexual and wall cell which include kitin and cellulose or both of them. Mushroom does not has capillary and chlorophyll, also reproduction with spore. This research is about Kinds of Macro Mushroom That Are Founded At palm garden Kenagarian Damar Rumput Kecamatan Airpura Kabupaten Pesisir Selatan have been done in January 2014. The method is used in this research that is observation and direct collection toward macro mushroom that is founded in research location. From the research is got 12 kinds of macro fungi At palm garden Kenagarian Damar Rumput Kecamatan Airpura Kabupaten Pesisir Selatan. From this research can be concluded that mushroom is founded At palm garden Kenagarian Damar Rumput Kecamatan Airpura Kabupaten Pesisir Selatan include in 3 classes such Agaricomycetes, Pezizomycetes and Gasteromycetes, 4 ordo, 7 family and also 9 genus.